Towards Targeted Delivery Systems: Ligand Conjugation Strategies for mRNA Nanoparticle Tumor Vaccines - Kyle K. L. Phua (Journal of Immunology Research)
The use of nanoparticles encapsulating messenger RNA (mRNA) as a vaccine has recently attracted much attention because of encouraging results achieved in many nonviral genetic antitumor vaccination studies. Notably, in all of these studies, mRNA nanoparticles are passively targeted to dendritic cells (DCs) through careful selection of vaccination sites. Hence, DC-targeted mRNA nanoparticle vaccines may be an imminent next step forward. In this brief report, we will discuss established conjugation strategies that have been successfully applied to both polymeric and liposomal gene delivery systems. We will also briefly describe promising DC surface receptors amenable for targeting mRNA nanoparticles. Practicable conjugation strategies and receptors reviewed in this paper will provide a convenient reference to facilitate future development of targeted mRNA nanoparticle vaccine.